Worlding the south Nineteenth-century literary culture and the southern settler colonies - Comyn, Sarah; Fermanis, Porscha (Manchester University Press, 2021)
This collection brings together for the first time literary studies of British colonies in nineteenth-century Australia, New Zealand, South Africa, South America, Southeast Asia, and the Pacific Islands. Drawing on hemispheric studies, Indigenous studies, and southern theory to decentre British and other European metropoles, the collection offers a latitudinal challenge to national paradigms and traditional literary periodisations and canons by proposing a new literary history of the region that is predicated less on metropolitan turning points and more on southern cultural perspectives in multiple regional centres from Cape Town to Dunedin. With a focus on southern orientations, southern audiences, and southern modes of addressivity, Worlding the south foregrounds marginal, minor, and neglected writers and texts across a hemispheric complex of southern oceans and terrains. Drawing on an ontological tradition that tests the dominance of networked theories of globalisation, the collection also asks how we can better understand the dialectical relationship between the 'real' world in which a literary text or art object exists and the symbolic or conceptual world it shows or creates. By examining the literary processes of 'worlding', it demonstrates how art objects make legible homogenising imperial and colonial narratives, inequalities of linguistic power, textual and material violence, and literary and cultural resistance. With contributions from leading scholars in nineteenth-century literary and cultural studies, the collection revises literary histories of the 'British world' by arguing for the distinctiveness of settler colonialism in the southern hemisphere, and by incorporating Indigenous, diasporic, settler, and other southern perspectives.